Warfarin and the Risk of Death, Stroke, and Major Bleeding in Patients With Atrial Fibrillation Receiving Hemodialysis: A Systematic Review and Meta-Analysis - Hong Lei; Li-Ting Yu; Wei-Ning Wang; Shun-Guo Zhang (Frontiers in Pharmacology, 2018)
Background: Up to date, the efficacy and safety of warfarin treatment in atrial fibrillation patients receiving hemodialysis remain controversial. So we performed this meta-analysis to try to offer recommendations regarding warfarin management in this population.Methods: We searched Pubmed, Embase, and Cochrane library and reviewed relevant reference lists from 1980 to March 2018. Studies were included if they described the risks of mortality, stroke, and bleeding events with or without warfarin in atrial fibrillation patients receiving hemodialysis.Results: Overall, the use of warfarin was not associated with mortality (OR = 0.95, 95%CI = 0.89–1.02), stroke (OR = 1.06, 95% CI = 0.87–1.30) and ischemic stroke (OR = 0.85, 95% CI = 0.68–1.05), but its use could increase the risks of hemorrhagic stroke (OR = 1.34, 95% CI = 1.13–1.59) and major bleeding (OR = 1.24, 95% CI = 1.14, 1.35). In subgroup analyses, when analyses were mainly restricted to atrial fibrillation patients who were undergoing hemodialysis and taking other anticoagulation agents, warfarin therapy didn't reduce the risks for mortality (OR = 0.98, 95% CI = 0.68–1.42) and ischemic stroke (OR = 1.03, 95% CI = 0.89–1.19), but significantly increased the risks of stroke (OR:1.14, 95% CI = 1.01–1.29) and bleeding events such as hemorrhagic stroke (OR = 1.42, 95% CI = 1.14–1.77) and major bleeding (OR = 1.24, 95% CI = 1.14–1.35). While in patients who didn't take other anticoagulation agents or aspirin, warfarin use was not associated with all-cause mortality (OR = 0.90, 95% CI = 0.78–1.04), or any stroke (OR = 1.00, 95% CI = 0.71–1.40). Its use was associated with significantly decreased risk of ischemic stroke (OR = 0.71, 95% CI = 0.60–0.85), but not associated with hemorrhagic stroke (OR = 1.45, 95% CI = 0.83–2.55). Besides, another subgroup analysis showed that warfarin therapy didn't exert a protective role in patients with normal serum lipid levels (OR = 1.04, 95% CI = 0.85–1.26), but seemed to decrease the risk of ischemic stroke in patients with hyperlipidemia (OR = 0.38, 95% CI = 0.11–1.29).Conclusion: Our results suggested that it was necessary to prescribe warfarin for the prevention of ischemic events in hemodialysis patients with atrial fibrillation, but if these patients were already prescribed with other anticoagulants for the treatment of other co-existing diseases, then warfarin was not recommended.